2023
DOI: 10.1002/adma.202303059
|View full text |Cite
|
Sign up to set email alerts
|

Organic Sonodynamic Materials for Combination Cancer Immunotherapy

Abstract: Sonodynamic therapy (SDT) has been a promising non‐invasive therapeutic modality to treat deep‐seated tumors owing to the good tissue penetration ability and spatiotemporal controllability of ultrasound (US); however, the low sonodynamic activity and potential side effects greatly limit its clinical translation. Cancer immunotherapy that leverages the immune system to fight against cancer has great potential to synergize with SDT for the treatment of cancer with high efficiency and safety. In this review, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…As expected, “caged” Tz-Ru1 could hardly generate ROS after US irradiation, while obvious typical signals corresponding to 1 O 2 , • OH and O 2 •– appeared in the ESR spectra of activated Tz-Ru1 after US irradiation. Collectively, these click-activated ruthenium­(II) sonosensitizers can efficiently produce ROS under US irradiation following both type I (electron transfer) and type II (energy transfer) pathways (Figure H), showing great potential to overcome hypoxic TME for improved SDT effect. …”
Section: Resultsmentioning
confidence: 99%
“…As expected, “caged” Tz-Ru1 could hardly generate ROS after US irradiation, while obvious typical signals corresponding to 1 O 2 , • OH and O 2 •– appeared in the ESR spectra of activated Tz-Ru1 after US irradiation. Collectively, these click-activated ruthenium­(II) sonosensitizers can efficiently produce ROS under US irradiation following both type I (electron transfer) and type II (energy transfer) pathways (Figure H), showing great potential to overcome hypoxic TME for improved SDT effect. …”
Section: Resultsmentioning
confidence: 99%
“…Undisputedly, after ultrasound irradiation, SPNs can transfer a portion of energy to oxygen or water molecules in the TME, generating ROS and causing tumor cell death. [29] It is worth noting that SPN-mediated tu-mor cell death is highly immunogenic, indicating that alongside tumor ablation, it triggers the production of high-quality tumor antigens and damage-associated molecular patterns (DAMPs). After SPN treatment, the activation of dendritic cells (DCs) is upregulated, promoting efficient antigen presentation and T cell education.…”
Section: Photophysical Properties Of Spnsmentioning
confidence: 99%
“…When the electrons return to the ground state, they can transfer energy to oxygen or water molecules in the TME, generate ROS, and induce tumor cell ICD. [29] Compared with NIR-light with a penetration depth of <1 cm, ultrasound can effectively penetrate at least 4 cm of tissue, enabling ultrasound-based tumor diagnosis and treatment strategies with a high potential for clinical translation. [84] In addition, it can also be combined with other cancer immunotherapy methods to achieve a synergistic effect and further improve the effect of cancer treatment.…”
Section: Sonodynamic Immunotherapymentioning
confidence: 99%
“…Unfortunately, the inherent shortcomings of photosensitizers, such as long-term skin sensitivity, low bioavailability, and poor stability, cannot be avoided, which limits the use of organic sonosensitizers in practical practice. 81–85 Inorganic sonosensitizers include titanium dioxide (TiO 2 ), zinc oxide (ZnO 2 ), black phosphorus (BP), Bi 2 MoO 6 , MnWO x , and so on. In many previous studies, inorganic sonosensitizers have been found to have superior physical and chemical properties and high stability and can provide more nucleation sites for cavitation bubbles by ultrasonic stimulation, resulting in continuous ROS generation.…”
Section: Sonosensitizersmentioning
confidence: 99%